Physical Characteristic and Palatability of Wafer Complete Ration Based on Sugar Cane Sprout and Bagasse on Friesen Holsteinâs Calves - Retnani, Y; Widiarti, W; Satoto, KB (ANIMAL PRODUCTION, 2011)
This research was aimed to study the physical characteristic and palatability of wafer complete ration based on sugar cane sprout and bagasse. Physical characteristic measured were water content, water activity and density. Data of physical characteristics were analyzed using Completely Randomize Design, with four treatments and three replications. Analysis data of palatabity test used were T-test method i.e., rations of R0 vs R1 R2 R3, ration of R1 vs R2, ration of R0 vs R3, ration of R3 vs R2. The treatment was wafer complete ration with different fiber source, i.e. R0 = 80% concentrate + 20% field grass; R1 = concentrate 80% + 20% bagasse; R2 = concentrate 80% + sugar cane sprout 10% + bagasse 10%; R3 = concentrate 80% + 20% sugar cane sprout. The data were analyzed using ANOVA and continued with Contrast Orthogonal Test. The result of this research showed that the wafer complete ration that contains sugar cane sprout had better physical characteristics. Palatability of wafer complete ration containing field grass and sugar cane sprout was more preferred than that containing combination of bagasse and sugar cane sprout. The average consumption of wafer complete ration on FHâs calf containing 20% of field grass was ranged at 44â48%, ration containing 20% of bagasse was at 6â10%, ration containing 10% of sugar cane sprout and 10% bagasse was at 13â16% and ration containing 20% of sugar cane sprout was at 30â33%. (Animal Production 13 (1):24-29 (2011)Key Words: physical characteristic, palatability, wafer, bagasse, sugar cane sprout.